The Evaluation of Athletic Extracurricular Management of Dr. Soetomo and Jalan Jawa Junior High School in Surabaya - Sulaiman Sulaiman; Amrozi Khamidi; Edy Mintarto (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
One of the fundamental strategies in attempts to develop athletic sports in Surabaya was to conduct special training through athletic extracurricular activities in schools, hence it was the starting point for the discovery of potential athletes. The purpose of this study was to determine the strengths, weaknesses, opportunities, and Threat from athletic extracurricular management which included Planning, Organizing, Implementing and Supervising which was conducted by Dr. Soetomo and Jalan Jawa Junior High School in Surabaya. The approach used in this study was a qualitative approach and the type of evaluative research (Evaluation Research) used descriptive methods. The evaluation design used in this study was the SWOT Analysis. The results and conclusions of this study indicated that the athletic extracurricular management at Dr Soetomo Junior High School; The Planning was already a good program, The Organizing used the organizational structure and cooperation which already existed so the working mechanism was clear of its functions and parts, The Actuating contained the schedule of activities, the attendance of students and the coaches are well-monitored by the extracurricular coordinator, The Controlling implemented a routine evaluation that carried out at the end of the school year, but for the achievements have not been as the expectation. On the other hand, Jalan Jawa Junior High School implemented the management as; The Planning of this school did not have a good program, The Organizing included the involved cooperation of leaders, teachers and parents of students was very good, The Actuating related to the exercise did not run well, The Oversight represented almost every championship in Surabaya, Jalan Jawa Junior High School got good marks. The researchers have conducted more in-depth analysis of the strengths, weaknesses, opportunities, and Threat of athletic extracurricular management which included Planning, Organizing, Implementing and Supervising which was conducted by Dr Soetomo and Jalan Jawa Junior High School in Surabaya, furthermore resulting some recommendations for Dr. Soetomo and Jalan Jawa Junior High School.